A cognitive study of metaphorical expressions of sadness in English and Vietnamese novels - Nguyễn Thị Lệ Thủy (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2024)
This study is aimed to study the conceptual metaphor of sadness in English and Vietnamese novels from 19th to 21st in the light of cognitive linguistics. The data of 305 samples including 144 in English and 161 in Vietnamese which are collected from English and Vietnamese novels from the Internet and in publication printings are categorized, analysed and compared to find out the similarities and differences in the conceptual metaphors of sadness. The findings reveal that there are 11 cases of conceptual metaphor of sadness found in both languages and there are 3 cases found only in Vietnamese. The frequency of each case is then compared to find out the similarities and differences of these conceptual metaphors between the two languages. The findings will serve as a foundation for a number of implications for English language teaching, learning, and translation practice.